Reading the Odyssey - Schein, Seth (Princeton University Press, 1996)
This wide-ranging collection makes available to specialists and nonspecialists alike important critical work on the Odyssey produced during the last half century. The ten essays address five major concerns: the poem's programmatic representation of social and religious institutions and values; its transformation of folktales and traditional stories into epic adventures; its representation of gender roles and, in particular, of Penelope; its narrative strategies and form; and its relation to the Iliad, especially to that epic's distinctive conception of heroism. In the introduction, Seth L. Schein describes the poetic background to the work and suggests a variety of interpretive approaches, some of which are developed in the essays that follow. These essays include previously published work by Jean-Pierre Vernant, Pierre Vidal-Naquet, Pietro Pucci, and Charles P. Segal. There also are a new essay by Laura M. Slatkin, two revised and expanded ones by Nancy Felson-Rubin and Michael N. Nagler, and three appearing in English for the first time by Uvo Hlscher, Karl Reinhardt, and Vernant. The result is a collection that juxtaposes older, often hard-to-find articles with significant newer pieces in a way that allows for a fruitful dialogue among them.
10.1515/9780691214146